1994
DOI: 10.1073/pnas.91.9.3670
|View full text |Cite
|
Sign up to set email alerts
|

A faster-acting and more potent form of tissue plasminogen activator.

Abstract: Current treatment with tissue painogen activator (tPA) requires an Intravenous infusion (1.5-3 h) became the clearance of tPA from the circulation is rapid (t1/2 6 min).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
220
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(226 citation statements)
references
References 34 publications
4
220
0
2
Order By: Relevance
“…A newer type of rTPA called tenecteplase was designed to be more resistant to inhibition by PAI‐1 to overcome the high level of inhibition 22. This product has been used in a single horse in combination with a DNase with a successful outcome 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A newer type of rTPA called tenecteplase was designed to be more resistant to inhibition by PAI‐1 to overcome the high level of inhibition 22. This product has been used in a single horse in combination with a DNase with a successful outcome 23…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a tentative treatment protocol is proposed: consider administration of IPFT if the pleural effusion remains above the level of the drain or is trapped in fibrin loculations 24 h after the placement of indwelling chest drains. Tenecteplase could be used in preference to alteplase, based on better theoretical performance in septic effusions 22. If using alteplase, 2–10 mg per dose q12–24 h for 3 days, with a dwell‐time of approximately 4 h is a recommended treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…A TNK-tPA dosage of 0.53 m a g was selected as the most appropriate for the ASSENT-2 trial!. l 6 ASSENT-2 was a Phase 111 trial that randomized 16,949 patients with AM1 and ST-segment elevation presenting within 6 h to a weight-optimized TNK-tPA regimen or t-PA.I7. Ix The study was designed to demonstrate equivalence between the drugs.…”
Section: Assent-2: An Equivalence Trialmentioning
confidence: 99%
“…The molecule also possesses 14-fold enhanced fibrin specificity than t-PA but comparable fibrin-binding affinity and plasma clot lysis activity in vivo. 89 Clinical trials showed no difference between t-PA and TNK-tPA in reducing infarct mortality during AMI, however, there was a decrease in major bleeding rate in comparison with t-PA. 92 In the TIMI 10B (Thrombolysis in Myocardial Infarction) trial a single bolus administration of TNK-tPA (40 mg) produced the same patency rate at 90 min of thrombolytic therapy as the accelerated regimen of alteplase. 93 In the ASSENT-1 (Assessment of Safety and Efficacy of a New Thrombolytic agent) trial, a single bolus (30 to 50 mg) administration of tenecteplase was found to be as safe as the accelerated alteplase administration regimen in the treatment of patients with AMI.…”
Section: Third Generation Plasminogen Activatorsmentioning
confidence: 99%
“…5 (ii) Tenecteplase (TNK-tPA) It is a variant of t-PA with 3 point mutations {(i) Thr 103 with Asn, (ii) Asn 117 with Gln and (iii) Lys 296 -His 297 -Arg 298 -Arg 299 each replaced with alanine} and a molecular weight of 65 kDa (527 residues). 89 The first mutation at position 103 introduces a glycosylation site while the second mutation deletes the glycosylation site within the kringle 1 domain which also prolongs its half-life to about 10-24 min since it is partly responsible for t-PA elimination. 90 Owing to its slow clearance rate, a single bolus regimen can be administered simplifying its application outside of a hospital setting.…”
Section: Third Generation Plasminogen Activatorsmentioning
confidence: 99%